2010
DOI: 10.1016/j.taap.2009.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-mediated signals modulate cell death and survival of T lymphocytes

Abstract: The capacity of nicotine to affect the behavior of non-neuronal cells through neuronal nicotinic acetylcholine receptors (nAChRs) has been the subject of considerable recent attention. Previously, we showed that exposure to nicotine activates the nuclear factor of activated T cells (NFAT) transcription factor in lymphocytes and endothelial cells, leading to alterations in cellular growth and vascular endothelial growth factor production. Here, we extend these studies to document effects of nicotine on lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
2
19
0
1
Order By: Relevance
“…Our data are consistent with previous studies showing that α7-nAChR-like radioligand binding sites are present in total lymphocyte populations (De Rosa et al, 2009, De Rosa et al, 2005, Sato et al, 1999, Yoshikawa et al, 2006), immortalized T cell lines (Oloris et al, 2009, Razani-Boroujerdi et al, 2007) and primary cultures of CD4 + T cells (Nizri et al, 2009). Our finding that nAChR α7 subunit message levels in T cells increase after MOG immunization suggests that levels of receptor-like binding sites also might increase in response to such a challenge and perhaps upon growth in primary cell culture or after immortalization (Oloris et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are consistent with previous studies showing that α7-nAChR-like radioligand binding sites are present in total lymphocyte populations (De Rosa et al, 2009, De Rosa et al, 2005, Sato et al, 1999, Yoshikawa et al, 2006), immortalized T cell lines (Oloris et al, 2009, Razani-Boroujerdi et al, 2007) and primary cultures of CD4 + T cells (Nizri et al, 2009). Our finding that nAChR α7 subunit message levels in T cells increase after MOG immunization suggests that levels of receptor-like binding sites also might increase in response to such a challenge and perhaps upon growth in primary cell culture or after immortalization (Oloris et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that nAChR α7 subunit message levels in T cells increase after MOG immunization suggests that levels of receptor-like binding sites also might increase in response to such a challenge and perhaps upon growth in primary cell culture or after immortalization (Oloris et al, 2009). Further work is needed to define the dynamics of nAChR expression in immune cells, as their mediation of nicotinic effects also could vary depending on conditions and models used.…”
Section: Discussionmentioning
confidence: 99%
“…However, disparate and sometimes conflicting reports as to the mechanisms of nicotinic cholinergic mediation of anti-inflammatory effects need to be reconciled before a complete understanding can be achieved. For example, exposure to nicotine has been reported to activate the nuclear factor of activated T cells transcription factor in lymphocytes and endothelial cells, resulting in alterations in cell growth and vascular endothelial growth factor production [153]. Additional studies suggest that nicotine stimulates COX-2 expression via the activation of NF- κ B and subsequent release of proinflammatory mediators, such as prostaglandin E2 (PGE2), IL-1 β , IL-6, nitric oxide, and TNF- α in human gingival fibroblasts [154, 155].…”
Section: Future Directionsmentioning
confidence: 99%
“…Furthermore, anti-inflammatory effects mediated by alpha7 nicotinic receptors can be synergistic with other signaling systems such as steroids and are mediated through reduction of nuclear translocation of p65 to suppress cytokine expression [156]. Nicotine has also been shown to have paradoxical effects that might alternatively enforce survival or trigger apoptosis, suggesting that depending on timing and context, nicotine might act either as a survival factor or as an inducer of apoptosis in normal or transformed lymphocytes, and possibly other nonneuronal cells [153]. Similar paradoxical effects have been reported for other targets involved in inflammation.…”
Section: Future Directionsmentioning
confidence: 99%
“…The effects of nicotine on cell proliferation, apoptosis and angiogenesis are mediated by nicotine’s interaction with the nAChR (6,7) and genome wide association study studies have implicated a gene locus (15q25) that encodes three nAChR subunits in lung cancer risk (1416). Some investigators have suggested this association is a direct link to lung cancer, independent from any effect on nicotine addiction and smoking intensity (7,17).…”
Section: Introductionmentioning
confidence: 99%